Language policies in Brazil and the epistemology underlying the selection of foreign language textbooks - Vieira, Gicele; Finardi, Kyria Rebeca (Árboles y Rizomas, 2019)
The aim of this paper is to discuss language policies in Brazil, especially in relation to the way they are implemented in the guidelines for the selection of textbooks for the teaching and learning of English as a foreign language (EFL). To subsidize the reflection herein proposed, the study analyzed the main principles and set of criteria used by the National Textbook Program (PNLD) to assess the textbooks designed for Brazilian secondary education. The results of the qualitative analysis carried out revealed a straightforward connection among modern foreign language learning policies in Brazil and the epistemology underlying the evaluation and choice of textbooks. The study concludes that a wider perspective on EFL teaching in Brazil is necessary, taking into account the need for the development of students’ speaking skills required in the exercise of a global citizenship.